Making art and the memory of place - Edom, Jascy-Leigh (Rhodes University, 2026)
This practice-led thesis examines my artmaking process, which is rooted in memory, remembrance, nostalgia and grief. I return to my grandfather’s neglected garden, a significant site of childhood memory and place attachment, as both subject and material source. Drawing on artist who engage with memory, materiality and loss, I contextualise the relationship between grief and place through a phenomenological lens. I paint with remnants from the garden - plants, spics and teas - as an ode to my grandfather and the time we shared. His influence shaped my love for art, and in this body of work I adopt a childlike approach, working with materials in their rawest form through imprinting, staining and carving. Over the course of this project, I have observed the materials gradually fade and decay, shifting from vibrancy to muted tones. This slow transformation became central to the methodology. The works function as living, dying entities that embody mourning as process rather than fixed state. By allowing organic matter to age naturally, the work challenges the permanence traditionally associated with painting and positions decay as both visual language and emotional framework. In this way, the paintings operate as a living archive of presence and absence, proposing a materially led phenomenologically informed approach to grief in contemporary art, where the life and entropy of the artwork mirror the lived experience of loss.
Keywords: Memory in art (http://id.loc.gov/authorities/subjects/sh97002102); Place attachment (http://id.loc.gov/authorities/subjects/sh2007001724); Grief in art (http://id.loc.gov/authorities/subjects/sh85057331); Families in art (http://id.loc.gov/authorities/subjects/sh85047050)